Comparing the effectiveness of capture and replay against automatic input generation for Android graphical user interface testing. (16th October 2020) - Di Martino, Sergio; Fasolino, Anna Rita; Starace, Luigi Libero Lucio; Tramontana, Porfirio
Summary: Exploratory testing and fully automated testing tools represent two viable and cheap alternatives to traditional test‐case‐based approaches for graphical user interface (GUI) testing of Android apps. The former can be executed by capture and replay tools that directly translate execution scenarios registered by testers in test cases, without requiring preliminary test‐case design and advanced programming/testing skills. The latter tools are able to test Android GUIs without tester intervention. Even if these two strategies are widely employed, to the best of our knowledge, no empirical investigation has been performed to compare their performance and obtain useful insights for a project manager to establish an effective testing strategy. In this paper, we present two experiments we carried out to compare the effectiveness of exploratory testing approaches using a capture and replay tool (Robotium Recorder) against three freely available automatic testing tools (AndroidRipper, Sapienz, and Google Robo). The first experiment involved 20 computer engineering students who were asked to record testing executions, under strict temporal limits and no access to the source code. Results were slightly better than those of fully automated tools, but not in a conclusive way. In the second experiment, the same students were asked to improve the achieved testing coverage by exploiting the source code and the coverage obtained in the previous tests, without strict temporal constraints. The results of this second experiment showed that students outperformed the automated tools especially for long/complex execution scenarios. The obtained findings provide useful indications for deciding testing strategies that combine manual exploratory testing and automated testing. Abstract : When testing Android Applications, are fully‐automated GUI exploration solutions more effective than capture‐and‐replay tools used by novice practitioners? In this empirical study, we compare these two approaches using state‐of‐the‐art automated GUI exploration tools and 20 students. Our results show that students with no prior experience on the applications under test are as effective as the best tools. When also given source code, the students outperform the tools. The findings provide useful indications for combining manual exploratory testing and automated testing.